Factors Associated With Early Reocclusion in Recanalized Intracranial Atherosclerotic Occlusion: ANGEL-REBOOT Insights - Li, Lei; Song, Shuang; Mo, Dapeng; Tong, Xu; Miao, Zhongrong; Gao, Feng (Stroke (1970), 2025)
BACKGROUND: Early reocclusion following successful recanalization through mechanical thrombectomy is linked to poor clinical outcomes in patients with stroke with intracranial atherosclerotic occlusion (ICAS-O). However, the factors influencing early reocclusion remain inadequately understood. This study is a post hoc analysis of 24-hour reocclusion in patients with successfully recanalized ICAS-O from a multicenter trial. METHODS: Patients with successfully recanalized ICAS-O were selected from the ANGEL-REBOOT trial (Randomized Study of Bailout Intracranial Angioplasty Following Thrombectomy for Acute Large Vessel Occlusion). Reocclusion was defined as a 24-hour arterial occlusive lesion score of 0 to 1, determined by magnetic resonance or computed tomography angiography. Possible factors associated with early reocclusion were screened through univariable analysis, and then, multivariable logistic regression was used to identify independent factors associated with early reocclusion. RESULTS: Among the 348 patients in the ANGEL-REBOOT trial, 21 could not be diagnosed with ICAS-O, 14 failed recanalization by the end of the procedure, and 14 had no follow-up angiography data. Finally, a total of 299 subjects were included, with a median age of 63 (interquartile range, 55-69) years, and 77 of 299 (25.75%) were female patients. The 24-hour reocclusion rate was 9.7% (29/299). Through backward elimination, 3 independent factors remained in the final multivariable logistic regression model. Specifically, puncture-to-recanalization time (per hour increase: odds ratio, 1.80 [95% CI, 1.31-2.47]) was positively associated with reocclusion, while general anesthesia (odds ratio, 0.25 [95% CI, 0.10-0.65]) and a postprocedural expanded Thrombolysis in Cerebral Infarction score of 2c-3 (odds ratio, 0.35 [95% CI, 0.14-0.85]) were negatively associated with reocclusion. Compared with patients without reocclusion, those with reocclusion had significantly greater 90-day modified Rankin Scale scores (median 4 versus 1, Mann-Whitney U test; P<0.001). CONCLUSIONS: In patients with successfully recanalized ICAS-O, a longer puncture-to-recanalization time was associated with an increased risk of early reocclusion, while general anesthesia and a postprocedural expanded Thrombolysis in Cerebral Infarction score of 2c-3 were associated with a reduced risk of early reocclusion. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: NCT05122286.